Meningkatkan Kesadaran Kritis terhadap Konten Digital dan Tantangan Etika dalam Pemanfaatan AI pada SMK PKP 1 Jakarta - Jiyan Suhada; Gigih Amrillah Ibnurhus; Faruk Muhamad (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2025)
This Community Service Program (PkM) arises from the significant challenges faced by Vocational High School (SMK) students in adapting to the rapid progression of the digital era and the widespread use of artificial intelligence (AI). In an environment flooded with online information, many students tend to accept and share digital content without adequately verifying its validity, leaving them susceptible to misinformation, deceptive media, and inaccurate data. Ethical risks linked to AI misuse have also surfaced, including plagiarism through automated text-generation tools, excessive reliance on chatbots without ethical consideration, and potential privacy breaches due to limited awareness of technological vulnerabilities. To respond to these issues, the PkM program adopts an educational strategy focused on critical digital literacy training and mentoring tailored for SMK students. The initiative highlights the importance of critical thinking in evaluating and validating digital information, while simultaneously promoting ethical responsibility in using AI. Through workshops, case-based simulations, group discussions, and practical content analysis, students learn to recognize digital manipulation and reflect on the social implications of AI. Expected outcomes include increased ethical digital awareness, the development of a sustainable training module, academic publications, and long-term collaboration between schools and universities, ultimately preparing students to be competent, ethical, and responsible digital citizens.